#### Answer

$\{(-2,3)\}$

#### Work Step by Step

1. No variable has 1 as a coefficient, there will be fractions...
Express y from the second equation (solve for y)
$9y=31+2x\qquad/\div 9$
$y=\displaystyle \frac{31+2x}{9}$
2. Substitute y in the other equation and solve.
$4x+5\displaystyle \cdot\frac{31+2x}{9}=7\qquad/\times 9$
... gets rid of the fraction ...
$36x+5(31+2x)=63$
$36x+155+10x=63\qquad/-155$
$46x=-92\qquad/\div 46$
$x=-2$
3. Back-substitute into the expression of y (step 1).
$y=\displaystyle \frac{31+2(-2)}{9}=\frac{27}{9}=3$
4. Write the solution as an ordered pair.
Solution set: $\{(-2,3)\}$